Polyelectrolyte microcapsules as ionic liquid reservoirs within ionomer membrane to confer high anhydrous proton conductivity - Zhang, H.; Wu, W.; Li, Y.; Liu, Y.; Wang, J.; Zhang, B.; Liu, Jian (Elsevier SA, 2015)
© 2015 Elsevier B.V. All rights reserved. Herein, novel composite membranes are prepared by embedding methacrylic acid polyelectrolyte microcapsules (PMCs) into sulfonated poly(ether ether ketone) (SPEEK) matrix, followed by impregnating imidazole-type ionic liquids (ILs). Within the composite membrane, the lumens of PMCs act as IL reservoirs, which provide large space for IL storage and thus significantly elevate the IL uptake. The IL leaching measurement suggests that the cross-linked shells of PMCs manipulate the IL release, endowing the composite membrane with high IL retention. Moreover, the high IL retention renders the composite membrane more anhydrous hopping sites (e.g., the imidazole groups on IL and the acid-base pairs between imidazole and sulfonic acid groups), imparting a facilitated proton conduction via Grotthuss mechanism. In particular, the composite membrane containing 12% PMCs achieves a high anhydrous proton conductivity of 33.7 mS cm-1at 150°C. The same membrane also exhibits a surprising steady-state IL retention of 36.9% after leaching in liquid water.